2004
DOI: 10.4049/jimmunol.173.2.721
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Pulmonary Immunopathology Mediated by Antigen-Specific Expression of TNF-α by Antiviral CD8+ T Cells

Abstract: Respiratory virus infection results in considerable pulmonary immunopathology, a component of which results from the host immune responses. We have developed a murine model to specifically examine the lung injury due to CD8+ T cell recognition of an influenza hemagglutinin (HA) transgene on lung epithelium in the absence of replicating virus, after adoptive transfer. Lung injury is largely mediated by chemokines expressed by the epithelial cells upon T cell recognition mediated by TNF-α. To determine the criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 27 publications
3
120
1
Order By: Relevance
“…28 The opposing conclusions regarding the role of TNF-␣ in influenza immunopathology drawn from this study and our current study are likely because the former used an adoptive transgenic T-cell transfer approach and a transgenic mouse model in which the bronchial epithelial cells overexpress hemagglutinin. 28 Two other studies have shown a decrease in disease severity in TNFR1 knockout mice infected with highly virulent H5N1 avian or a reconstructed 1918 pandemic influenza virus. In agreement with our study, these studies report the lack of involvement of TNFR1 in influenza viral clearance.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…28 The opposing conclusions regarding the role of TNF-␣ in influenza immunopathology drawn from this study and our current study are likely because the former used an adoptive transgenic T-cell transfer approach and a transgenic mouse model in which the bronchial epithelial cells overexpress hemagglutinin. 28 Two other studies have shown a decrease in disease severity in TNFR1 knockout mice infected with highly virulent H5N1 avian or a reconstructed 1918 pandemic influenza virus. In agreement with our study, these studies report the lack of involvement of TNFR1 in influenza viral clearance.…”
Section: Discussionmentioning
confidence: 60%
“…[23][24][25][26][27] In this regard, the limited data also suggest that production of TNF-␣ by influenza-specific CD8 T cells may contribute to lung immunopathology. 28,29 The immune-activating role of TNF-␣ was also shown in the models of other viral infections. 30,31 However, recent emerging evidence has suggested an immune regulatory nature of TNF-␣.…”
mentioning
confidence: 92%
“…þ T-cell bulk lines and clones were activated in vitro prior to adoptive transfer (43), and injected via the tail vein. Weight loss was monitored daily, and lungs were harvested at appropriate times for histology or chemokine analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The enhanced inflammatory response and leukocyte recruitment occurring after infection with highly pathogenic strains of influenza has been suggested to be dependent on TNF-and i-NOS-producing dendritic cells, as well as the CCR2 receptor (1,23). Epithelial CCL2 is rapidly induced in response to CD8 þ T-cell recognition in vitro and in vivo (32,43,45), and appears to require both TNF receptors, TNF-R1 and TNF-R2 (24).…”
mentioning
confidence: 99%
“…The initial inflammatory infiltrate helps control viral replication until the virus is cleared by a viral-specific, CTL-mediated response [4,5]. However, the inflammatory response to a respiratory infection may sometimes be detrimental to the host, causing augmented lung pathology [6,7]. Identifying factors involved in the recruitment of proinflammatory leukocytes will further our understanding of the inflammatory response and immunopathology associated with respiratory viral infections.…”
Section: Introductionmentioning
confidence: 99%